1997
DOI: 10.1046/j.1471-4159.1997.69030920.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of Brain Protein Phosphatase 1 with Cytoskeletal Targeting/Regulatory Subunits

Abstract: Protein phosphatase 1 catalytic subunit (PP1c) is highly enriched in isolated rat postsynaptic densities. Gel overlay analyses using digoxigenin (DIG)-labeled PP1revealed four major rat brain PP1~-binding proteins (PP1 bps) with molecular masses of~m216, 175, 134, and 75 kDa, which were (1) more abundant in brain than other rat tissues; (2) differentially expressed in microdissected brain regions; and (3) enriched in isolated cortex postsynaptic densities. PPlbpl75, PPlbpl34, PPlbp75, and PP1~were partially re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 25 publications
0
30
0
Order By: Relevance
“…Prior studies showed that anti-neurabin immune complexes from rat brain contained PP1␥1 but excluded PP1␤ (23). Far Westerns of brain extracts using recombinant PP1 catalytic subunits as probes suggested that neurabins displayed a significant preference for PP1␥1 and PP1␣ over PP1␤ (24). Our studies highlighted a domain in both neurabins that displayed PP1 isoform selectivity similar to the native proteins.…”
mentioning
confidence: 52%
“…Prior studies showed that anti-neurabin immune complexes from rat brain contained PP1␥1 but excluded PP1␤ (23). Far Westerns of brain extracts using recombinant PP1 catalytic subunits as probes suggested that neurabins displayed a significant preference for PP1␥1 and PP1␣ over PP1␤ (24). Our studies highlighted a domain in both neurabins that displayed PP1 isoform selectivity similar to the native proteins.…”
mentioning
confidence: 52%
“…Antibodies-The following primary antibodies were used for immunoblotting (dilutions indicated) and/or for immunoprecipitation: whole serum and affinity-purified sheep and rabbit anti-PP1␥ 1 and anti-PP1␤ (7,36,37); mouse anti-tyrosine hydroxylase (ImmunoStar, 1:1000); mouse anti-PP2Ac (BD Transduction Laboratories, 1:4000); rabbit antibody to spinophilin (8) purified using protein A-Sepharose (Upstate); and mouse anti-spinophilin (BD Transduction Laboratories, 1:1000). Secondary antibodies were from Promega (goat antimouse HRP, 1:2000; goat anti-rabbit HRP, 1:4000), AlphaQuest (rabbit anti-goat HRP, 1:4000), or Santa Cruz Biotechnology (goat anti-mouse HRP or donkey anti-sheep HRP preadsorbed with human and/or mouse IgG, 1:5000).…”
Section: Methodsmentioning
confidence: 99%
“…VIIA1). Notably, the PP1 binding module of Neurabins discriminates between PP1 isoforms, in that it prefers the ␣-subtype isoforms PP1␥ 1 and PP1␣ over PP1␤ (87,236,360). Finally, the COOH-terminal third of Neurabins includes a putative coiled-coil module and that of vertebrate Neurabin-I and of invertebrate Neurabins also a sterile ␣-motif.…”
Section: A Neurabin-associated Pp1mentioning
confidence: 99%